Patient And phaRmacist Telephonic Encounters (PARTE) in an underserved rural population with asthma: methods and rationale - Henry N. Young, PhD; S. Nadra Havican, BSPharm, RN, BCPS; Betty A. Chewning, PhD; Christine A. Sorkness, PharmD; Xin Ruppel, PharmD, BCPS, MBA; Sara Griesbach, PharmD, BCPS, AE-C (University of Minnesota Libraries Publishing, 2011)
Purpose: Methods used to deliver and test a pharmacy-based asthma care telephonic service for an underserved, rural patient population are described. Summary: In a randomized controlled trial (RCT), the Patient And phaRmacist Telephonic Encounters (PARTE) project is assessing the feasibility, acceptability, and preliminary impact of providing pharmacy-based asthma care service telephonically. The target audience is a low income patient population across a large geographic area served by a federally qualified community health center. Ninety-eight participants have been randomized to either standard care or the intervention group who received consultation and direct feedback from pharmacists via telephone regarding their asthma self-management and medication use. Pharmacists used a counseling framework that incorporates the Indian Health Services 3 Prime Questions and the RIM Technique (Recognition, Identification, and Management) for managing medication use problems. Pharmacists encouraged patients to be active partners in the decision-making process to identify and address the underlying cause of medication use problems. Uniquely, this trial collected process and summative data using qualitative and quantitative approaches. Pharmacists' training, the fidelity and quality of pharmacists' service delivery, and short term patient outcomes are being evaluated. This evaluation will improve our ability to address research challenges and intervention barriers, refine staff training, explore patient perspectives, and evaluate measures' power to provide preliminary patient outcome findings. Conclusion: A mixed method evaluation of a structured pharmacist intervention has the potential to offer insights regarding staff training, service fidelity and short term outcomes using quantitative and qualitative data in an RCT. Results will provide evidence regarding the feasibility and quality of carrying out the study and service delivery from the multiple perspectives of participants, clinicians, and researchers.